Social Support as Moderator for Psychological Adjustment, Anxiety, Stress, Depression and Its Interrelationship with Suicidal Ideation among Students Post-Outbreak of Covid-19 in Malaysia - Asma Perveen, Hazalizah binti Hamzah, Aroyewun Temitope Folashade (Tanjung Malim, 2024)
Social Support as Moderator for Psychological Adjustment, Anxiety, Stress, Depression and Its Interrelationship with Suicidal Ideation among Students Post-Outbreak of Covid-19 in Malaysia by Asma Perveen, Hazalizah binti Hamzah, Aroyewun Temitope Folashade